2020
DOI: 10.1111/jonm.12969
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the impact of ‘missed care’ in primary, community and nursing home settings

Abstract: Appropriate nursing staffing levels are critical to the delivery of safe and effective care. The planning and delivery of safe and effective care is complex. 'Safe and effective staffing' means that health and care services have the right numbers, with the right skills, in the right place at the right time (RCN, 2018). Having the right number of appropriately qualified, competent and experienced nurses has been reported to lead to improved patient outcomes, reduced mortality rates and increased productivity. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 34 publications
3
39
0
1
Order By: Relevance
“…Rather, it results from the conditions of possibility that are influenced, as they said, not only by a multitude of political-organizational factors related to the care organization model as a whole and the operational and care management but also by factors related to the complex nature of caring for the person and their family caregivers. The nature of the factors is consistent with that found by Sworn and Booth (2020) in a recent systematic review on the impact of missed care in community settings. The nurses reported the problems they encountered, and it is implicit in their interviews that the different aspects of structure, process, and outcome influence each other.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Rather, it results from the conditions of possibility that are influenced, as they said, not only by a multitude of political-organizational factors related to the care organization model as a whole and the operational and care management but also by factors related to the complex nature of caring for the person and their family caregivers. The nature of the factors is consistent with that found by Sworn and Booth (2020) in a recent systematic review on the impact of missed care in community settings. The nurses reported the problems they encountered, and it is implicit in their interviews that the different aspects of structure, process, and outcome influence each other.…”
Section: Discussionsupporting
confidence: 86%
“…Studies on this topic suggest that the main factors influencing the prevalence of missed care are related to the nurses' working environment, the demands associated with the patients' severity status, and the number of nurses available to provide such care (Phelan et al, 2018a). Only a few studies have explored community-based nursing care and even fewer have analyzed the phenomenon in home care settings (Sworn & Booth, 2020). This study aims to explore nurses' perspectives on the reasons for missed care or care that is not provided as frequently as expected to dependent people referred to home-based long-term care teams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts have been made to enhance the quality of community‐based health care (Mathieson et al., 2019 ). However, there are several reports of inadequate care and adverse events (Phelan et al., 2018 ; Sworn & Booth, 2020 ). These indicate a need to address questions about health care and the required clinical skill levels of staff members.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, work on missed care in community nursing contexts lags far behind that in the acute sector. Indeed, a recent systematic review of missed care in the community context (Sworn & Booth, 2019) identified only five empirical studies (reported in eight publications), undertaken in Ireland (Phelan & McCarthy, 2016;Phelan et al, 2018aPhelan et al, , 2018b, Australia (Blackman, Henderson, Willis, & Toffoli, 2015;Henderson, Willis, Blackman, Toffoli, & Verrall, 2016;Henderson, Willis, Xiao, & Blackman, 2017;Willis et al, 2016) and the United States (Nelson & Flynn, 2015). Collectively, this small body of research provides early insight into the prevalence of, types of and reasons for missed care in community nursing and care home settings.…”
mentioning
confidence: 99%